Linear and nonlinear resonant properties of electron gas in n-InSb and graphene layers in terahertz range in bias magnetic fields - V Grimalsky; Yu Rapoport; S Koshevaya; A Nosich; J Escobedo-Alatorre (Materials Research Express)
The nonlinear conductivity of 2D electron gas in graphene and 3D electron gas in the narrow-gap n- InSb semiconductor has been simulated in terahertz (THz) range by various methods including the direct quantum approach, the quasi-classical kinetics, and the quasi-relativistic hydrodynamics. These methods yield the same results under the electron temperatures ≤100 K when the kinetic electron effective mass used in the nonlinear hydrodynamics is equal to the effective mass in n- InSb and it is equal to some nonzero mass that depends on 2D electron concentration in the graphene. The linear resonant dependencies of the complex electron conductivity are simulated both from the kinetic theory and from the hydrodynamic one. The kinetic dependencies of the resonant conductivity on frequency coincide with ones obtained from the hydrodynamic theory under realistic electron concentrations and collision frequencies. Thus, the nonlinear hydrodynamic equations are valid to describe the nonlinear dynamics of the electron gas in graphene and in n- InSb. The nonlinear hydrodynamics has been applied for simulations of nonlinear propagation of THz electromagnetic waves through the multilayer structures dielectric - graphene or n- InSb - dielectric placed in a bias magnetic field. The simplest three-layer structures demonstrate the sharp nonlinear switching of the transparency of THz waves and the bistability under relatively low values of amplitudes of the incident electromagnetic wave.